Responses of the Warsaw Stock Exchange to the U.S. Macroeconomic Data Announcements - Gurgul, Henryk; Suliga, Milena; Wójtowicz, Tomasz (Managerial Economics, 2012)
The relationship between information flows and changes in asset prices is one of the main is- sues of financial economics. A fundamental assumption of the market efficiency hypothesis is that investors react to new information as it arrives. This reaction results in price changes that reflect investor`s expectations concerning the level of risk and rates of return. The main aim of this paper is to investigate the effect of U.S. macroeconomic data announcements about inflation, industrial production and unemployment on the trading volume and prices of the most liquid stocks listed on the Warsaw Stock Exchange in the period 2004-2011. Using event study methodology we determine when and how forecasts and investor expectations regarding future market conditions changes under the influence of incoming macroeconomic data on the U.S. economy. This methodology also allows us to describe the strength, direction and length of the impact of announcements about these macroeconomic indicators.